Facility and home based HIV Counseling and Testing: a comparative analysis of uptake of services by rural communities in southwestern Uganda - Guerra Ranieri; Abdulaziz Aden S; Mulogo Edgar M; Baine Sebastian O (BMC, 2011)
Abstract Background In Uganda, public human immunodeficiency virus (HIV) Voluntary Counseling and Testing (VCT) services are mainly provided through the facility based model, although the home based approach is being promoted as a strategy for improving access to VCT. However the uptake of VCT varies according to service delivery model and is influenced by a number of factors. The aim of this study therefore, was to compare predictors for uptake of facility and home based VCT in a rural context. Methods A longitudinal study with cross-sectional investigative phases was conducted at two sites (Rugando and Kabingo) in southwestern Uganda between November 2007 (baseline) and March 2008 (follow up). During the baseline visit, facility based VCT was offered at the main health centre in Rugando while home based VCT was offered at the household level in Kabingo and a mixed survey questionnaire administered to the respondents. The results presented in this paper are derived from only the baseline data. Results Nine hundred ninety four (994) respondents were interviewed, of whom 500 received facility based VCT in Rugando and 494 home based VCT in Kabingo during the baseline visit. The respondents had a mean age of 32.2 years (SD 10.9) and were mainly female (68 percent). Clients who received facility based VCT were less likely to be residents of the more rural households (adjusted Odds Ratio (aOR) = 0.14, 95% CI 0.07, 0.22). The clients who received home based VCT were less likely to report having an STI symptom (aOR = 0.63, 95% CI 0.46, 0.86), and more likely to be worried about discrimination if they contracted AIDS (aOR = 1.78, 95% CI 1.22, 2.61). Conclusion The uptake of VCT provided through either the facility or home based models is influenced by client characteristics such as proximity to service delivery points, HIV related symptoms, and fear of discrimination in rural Uganda. Interventions that seek to improve uptake of VCT should provide potential clients with both facility and home based VCT options within a given setting. The clients are then able to select a model for VCT that best fits their characteristics. This is likely to have positive implications for both service coverage and uptake by different sub-groups within particular communities.